METODE DAN STRATEGI PEMBELAJARAN DALAM PIAUD - Lydia Sartika; Neni Afriani (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Teaching and learning activities both have goals to be achieved. This goal can be achieved through strategy. Strategy is an effort made to achieve a goal. In teaching and learning activities, these strategies are called learning strategies. Learning strategies help teachers to build appropriate learning models. Learning strategies focus on what teachers and students do, not only providing and mastering theory, but also paying attention to students' life skills. Learning strategies can provide various activities that directly involve students to become more active and responsive. The learning process in class focuses on children's ability to remember information; Children's brains are forced to remember and store various information without having to understand the information they remember to relate it to everyday life. Learning strategies focus on what teachers and students do, not only providing and mastering theory, but also paying attention to students' life skills. Using appropriate teaching methods that suit the child's personality can create conditions for the child to develop his potential and abilities so that positive behavior develops within him.